Preparation, Structural Features and in vitro Immunostimulatory Activity of a Glucomannan From Fresh Dendrobium catenatum Stems - Liu, Jingjing; Yu, Luyao; Wang, Chun; Zhang, Yuefan; Xi, Hangxian; Si, Jinping; Zhang, Lei; Yan, Jingkun (Frontiers in Nutrition, 2022)
Dendrobium catenatum polysaccharides (DCPs) have attracted attention due to their multiple physiological activities and health benefits. In this study, a novel water-soluble DCP was obtained from fresh D. catenatum stems through three-phase partitioning and ethanol precipitation at room temperature. Its structural characteristics, rheological property, and in vitro immunostimulatory activity were evaluated. Results demonstrated that DCP was a homogenous polysaccharide with a carbohydrate content of 92.75% and a weight-average molecular weight of 2.21×105 Da. This polysaccharide is an O-acetylated glucomannan comprised by glucose, mannose, and galacturonic acid in a molar ratio of 39.2:69.5:0.3 and mainly comprises (1→4)-β-D-mannopyranosyl (Manp), 2-O-acetyl-(1→4)-β-D-Manp, (1→6)-α-D-glucopyranosyl (Glcp), and (1→4)-α-D-Glcp residues. DCP exhibits an extended rigid chain in an aqueous solution and favorable steady shear fluid and dynamic viscoelastic behaviors. In vitro immunostimulating assays indicated that DCP activates RAW264.7 cells, thus markedly promoting macrophage proliferation and phagocytosis and increasing the levels of nitric oxide, interferon-γ, interleukin-6, and interleukin-1β.